Determination Of Bioactive Compounds In Ulva Reticulata Extract Using Gc-Ms Technique - V. Sivaranjani, T.Malarvili, K. Suganthi, S.Mahalakshmi (International Journal of Modern Agriculture, 2021)
The bioactive components of Ulva reticulata have been evaluated using GC/MS. The chemical compositions of the ethanolic extract of Ulva reticulata was investigated using Gas Chromatography–Mass Spectrometry (Perkin-Elmer), while the mass spectra of the components found in the extract was compared with the National Institute of Standards and Technology (NIST) library. The GC-MS analysis revealed the presence of prevailing compounds like Hoslundin, 2,4,6-Tris-(1-phenylethyl)-phenol, 1,2-Benzenedicarboxylic acid , Alpha.-Ergostenol, Stigmasterol and Gamma.-Sitosterol in the ethanolic extract of Ulva reticulata. These findings support the traditional use of Ulva reticulata in various disorders.